Leveraging Positive Behavior Supports to Improve Engagement in Virtual Settings. Issue 2 (June 2021) - Speight, Renee; Kucharczyk, Suzanne
High-levels of classroom engagement and on-task behavior have been linked to positive outcomes for students. In traditional classroom settings when levels of on-task behaviors are low, teacher integration of Positive Behavior Interventions and Supports (PBIS) can facilitate improvement in student engagement. PBIS strategies such as creating clear routines and expectations, explicit instruction on expected behaviors, acknowledging behavior, and a high level of opportunities to respond have demonstrated efficacy for improving engagement across grade levels. As teachers increasingly adjust their teaching to virtual platforms these evidence-based practices should continue to be a part of their instructional repertoire. Unfortunately, teachers may have little experience in leveraging such practices to improve engagement in virtual classrooms. With the recent shift to virtual instruction due to the pandemic, it is important teachers are equipped with knowledge and skills to implement PBIS in virtual classroom settings to improve student outcomes. This manuscript provides a how-to guide to support teachers and administrators in effective and efficient use of PBIS in online platforms to bridge the gap in practice. Steps and an implementation checklist are included to improve virtual learning engagement by utilizing tools within online platforms such as Zoom and GSuite to clarify virtual expectations and increase student demonstration of expected behaviors.